Applying the RE-AIM framework to the Alberta's Caring for Diabetes Project: a protocol for a comprehensive evaluation of primary care quality improvement interventions. Issue 5 (26th October 2012) - Wozniak, Lisa; Rees, Sandra; Soprovich, Allison; Al Sayah, Fatima; Johnson, Steven T; Majumdar, Sumit R; Johnson, Jeffrey A
Abstract : Introduction: Diabetes represents a major public health and health system burden. As part of the Alberta's Caring for Diabetes (ABCD) Project, two quality-improvement interventions are being piloted in four Primary Care Networks in Alberta. Gaps between health research, policy and practice have been documented and the need to evaluate the impact of public health interventions in real-world settings to inform decision-making and clinical practice is paramount. In this article, we describe the application of the RE-AIM framework to evaluate the interventions beyond effectiveness. Methods and analysis: Two quality-improvement interventions were implemented, based on previously proven effective models of care and are directed at improving the physical and mental health of patients with type-2 diabetes. Our goal is to adapt and apply the RE-AIM framework, using a mixed-methods approach, to understand the impact of the interventions to inform policy and clinical decision-making. We present the proposed measures, data sources and data management and analysis strategies used to evaluate the interventions by RE-AIM dimension. Ethics and dissemination: Ethics approval for the ABCD Project has been granted from the Health Research Ethics Board (HREB #PRO00012663) at the University of Alberta. The RE-AIM framework will be used to structure our dissemination activities by dimension. Results: It will be presented at relevant conferences and prepared for publication in peer-reviewed journals. Various products, such as presentations, briefing reports and webinars, will be developed to inform key stakeholders of the findings. Presentation of findings by RE-AIM dimension will facilitate discussion regarding the public health impact of the two interventions within the primary care context of Alberta and lessons learned to be used in programme planning and care delivery for patients with type-2 diabetes. It will also promote the application of evaluation models to better assess the impact of community-based primary healthcare interventions through our dissemination activities.